Arthur Posnansky, the Czar of Tiwanaku Archaeology - Marsh, Erik Johnson (2019)
Arthur Posnansky was the illustrious pioneer of Tiwanaku archaeology, remembered as a quixotic, flamboyant, and swashbuckling character. He was a naval officer, a businessman, and a scholar. He dedicated nearly fifty years of his life to the study of the Andean past, which resonates through the history of Bolivian archaeology. While clearly not the field?s father, his commanding presence and outsized legacy could make him the czar of Tiwanaku archaeology. He developed a hyperbolic narrative of Tiwanaku as the ?cradle of American man? and tirelessly promoted it in Europe and the Americas. Like many pioneers, he was not trained as an archaeologist. His theories were based on little concrete information but he defended them with enviable passion. His ideas were strongly influenced by intellectual trends he lived though and participated in, including racist anthropology. This has led some to dismiss him as a misguided, self-appointed champion of Tiwanaku. However, I suggest that Posnansky?s life and times are very relevant to both understanding popular views and scholarly interpretations of the site.